Nuclear decommissioning costs: The impact of recoverability risk on valuation - D'Souza, Julia; Jacob, John; Soderstrom, Naomi S. (Journal of Accounting and Economics, 2000)
Mounting nuclear plant decommissioning costs and utility deregulation focused attention on accounting for decommissioning liabilities. FASB's Exposure Draft 158-B proposes balance sheet recognition of the projected future decommissioning cost liability at initial plant commission. We expect market valuation of each dollar of decommissioning cost apportioned to utilities to vary with utility-specific factors related to the probability of cost recovery via rates. We find a more negative decommissioning cost/firm value association for utilities with higher business or financial risk. Also, equity value is significantly associated with total decommissioning cost across all nuclear units in which a utility has ownership interest.